2021
DOI: 10.1029/2020je006800
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution of Electrostatic Electron Cyclotron Harmonic Waves in Saturn's Magnetosphere: A Survey of Over‐13‐Year Cassini RPWS Observations

Abstract: Electron cyclotron harmonic (ECH) waves are electrostatic emissions observed in bands between the harmonics (n) of electron gyrofrequency (f ce ), with dominant wave power centered around (n + 1/2) f ce (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…with the peaking amplitude at   7.7 8.5 L (Long et al, 2021;Menietti et al, 2008Menietti et al, , 2017Tao et al, 2010). The important role of ECH waves in producing Earth's diffuse auroral precipitation has been proposed in previous studies (Horne & Thorne, 2000;Horne et al, 2003;Meredith et al, 2009;Ni et al, 2016;Zhang et al, 2015).…”
Section: Teng Et Almentioning
confidence: 75%
See 1 more Smart Citation
“…with the peaking amplitude at   7.7 8.5 L (Long et al, 2021;Menietti et al, 2008Menietti et al, , 2017Tao et al, 2010). The important role of ECH waves in producing Earth's diffuse auroral precipitation has been proposed in previous studies (Horne & Thorne, 2000;Horne et al, 2003;Meredith et al, 2009;Ni et al, 2016;Zhang et al, 2015).…”
Section: Teng Et Almentioning
confidence: 75%
“…The averaged amplitudes of Saturnian ECH wave show a pronounced MLT asymmetry, with the nightside amplitude larger than those on the dayside. For the fundamental band, the averaged amplitudes are about 0.01–0.1 mV/m, with the peaking amplitude at L7.78.5 (Long et al., 2021; Menietti et al., 2008, 2017; Tao et al., 2010). The important role of ECH waves in producing Earth's diffuse auroral precipitation has been proposed in previous studies (Horne & Thorne, 2000; Horne et al., 2003; Meredith et al., 2009; Ni et al., 2016; Zhang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ECH waves can strongly interact with electrons and significantly affect electron dynamics in the terrestrial magnetosphere (Horne, 2015; Horne & Thorne, 2000), just like other wave modes such as chorus (Guo et al., 2020; He et al., 2021; Jin et al., 2018; S. Liu et al., 2020; Q. Yang et al., 2016), electromagnetic ion cyclotron wave (Guan et al., 2020; C. Yang et al., 2021) and auroral kilometric radiation (Xiao et al., 2022; S. Zhang et al., 2020, 2021). ECH waves generally exhibit banded structures (Fredricks, 1971; Shaw & Gurnett, 1975) with wave power preferentially distributed in the first harmonic band (e.g., Belmont et al., 1983; Long et al., 2021; Lou et al., 2018; Ni et al., 2017; Ni, Thorne, Liang, et al., 2011). Numerous works have demonstrated that the first‐band ECH can be in resonance with electrons at energies of ∼keV, causing the precipitation of diffuse auroral electrons (Fukizawa et al., 2020, 2022; Lou et al., 2021; Ni et al., 2012; Ni, Thorne, Horne, et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al, 2016), electromagnetic ion cyclotron wave (Guan et al, 2020; and auroral kilometric radiation (Xiao et al, 2022;. ECH waves generally exhibit banded structures (Fredricks, 1971;Shaw & Gurnett, 1975) with wave power preferentially distributed in the first harmonic band (e.g., Belmont et al, 1983;Long et al, 2021;Lou et al, 2018;Ni et al, 2017;Ni, Thorne, Liang, et al, 2011). Numerous works have demonstrated that the first-band ECH can be in resonance with electrons at energies of ∼keV, causing the precipitation of diffuse auroral electrons (Fukizawa et al, 2020(Fukizawa et al, , 2022Lou et al, 2021;Ni et al, 2012;Ni, Thorne, Horne, et al, 2011).…”
mentioning
confidence: 99%
“…Saturnʼs magnetosphere hosts a variety of plasma waves, e.g., whistler-mode waves (Menietti et al 2013(Menietti et al , 2014Woodfield et al 2022), electron cyclotron harmonic (ECH) waves (Tao et al 2010;Menietti et al 2017;Long et al 2021;Teng et al 2021), and Z-mode waves (Ye et al 2009(Ye et al , 2010Menietti et al 2016;Wu et al 2021). Via resonant wave-particle interactions, these waves are recognized to contribute significantly to the local acceleration and loss of Saturnʼs radiation belt electrons (e.g., Menietti et al 2012;Gu et al 2013;Kollmann et al 2018;Woodfield et al 2018Woodfield et al , 2019Yu et al 2019;Yao et al 2021;Woodfield et al 2022).…”
Section: Introductionmentioning
confidence: 99%